2004
DOI: 10.1044/1092-4388(2004/019)
|View full text |Cite
|
Sign up to set email alerts
|

A Prosodically Controlled Word and Nonword Repetition Task for 2- to 4-Year-Olds

Abstract: Citation: Roy, P. & Chiat, S. (2004). A prosodically controlled word and nonword repetition task for 2-to 4-year-olds: Evidence from typically developing children. Journal of Speech, Language, and Hearing Research, 47(1), pp. 223-234. doi: 10.1044/1092-4388(2004 This is the accepted version of the paper.This version of the publication may differ from the final published version. An association has been found between nonword repetition and language skills in school-aged children with both typical and atypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
122
1
14

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(149 citation statements)
references
References 31 publications
12
122
1
14
Order By: Relevance
“…NWR studies involve a nonsense word being read aloud to the child, who is asked to repeat it back accurately. Across a range of studies, NWR performance has consistently been shown to improve with age and to be inversely related to nonword length (e.g., Gathercole & Adams, 1993;Gathercole & Baddeley, 1989;Roy & Chiat, 2004). These results appeared to support the view that phonological WM capacity increased with age (e.g., Gathercole & Adams, 1993;Gathercole & Baddeley, 1989).…”
Section: Introductionsupporting
confidence: 76%
“…NWR studies involve a nonsense word being read aloud to the child, who is asked to repeat it back accurately. Across a range of studies, NWR performance has consistently been shown to improve with age and to be inversely related to nonword length (e.g., Gathercole & Adams, 1993;Gathercole & Baddeley, 1989;Roy & Chiat, 2004). These results appeared to support the view that phonological WM capacity increased with age (e.g., Gathercole & Adams, 1993;Gathercole & Baddeley, 1989).…”
Section: Introductionsupporting
confidence: 76%
“…Our method is based on non-word repetition tasks that are widely used in studies of spoken language acquisition (Dollaghan & Campbell, 1998;Gallon, Harris, & van der Lely, 2007;Gathercole & Baddeley, 1990;Kirk & Demuth, 2006;Roy & Chiat, 2004). The participant is required to listen to a set of non-words and repeat each one immediately after hearing it.…”
Section: Non-word Repetition As a Tool For Investigating Phonologicalmentioning
confidence: 99%
“…In spoken language research, two manipulations of non-word items have been carried out: the quantity of phonological material, achieved by manipulating the number of syllables (Gathercole & Baddeley, 1990;Dollaghan & Campbell, 1998), and the nature of that phonological material, achieved by manipulating the segmental content, syllabic complexity and/or metrical structure of that material (de Bree, 2007;Gallon, Harris, & van der Lely, 2007;Kirk & Demuth, 2006;Marshall & van der Lely, 2009;Roy & Chiat, 2004). There is evidence that both the quantity of phonological material and the nature of the phonological representation to be encoded impact on accuracy in this task -participants are less accurate as length and complexity increase, and this is the case for children with typical and atypical language development.…”
Section: Non-word Repetition As a Tool For Investigating Phonologicalmentioning
confidence: 99%
“…Results have demonstrated that the test is an excellent task not only for measuring phonological memory but also for evaluating children's language development since scores on nonword repetition correlate positively and significantly with other standard measures of language development such as vocabulary level. This is supported by works conducted in English (Gathercole & Baddeley, 1989;Hoff, Core & Bridges, 2008;Roy & Chiat, 2004), Spanish (Mariscal & Gallego, 2013;Rujas, 2014), Dutch (Rispens & Baker, 2012), or Italian (D'Odorico, Assanelli, Franco & Jacob, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has frequently been suggested that the relationship between nonword repetition and word learning is reciprocal (Bishop, 2006), since having an extensive vocabulary impacts on the ability to efficiently segment words and store them in the memory. As well as vocabulary level, a large number of other variables affecting repetition accuracy have been identified: lexical status (Hoff, et al, 2008;Mariscal & Gallego, 2013;Roy & Chiat, 2004; syllabic length (Ebert, Kalanek, Cordero & Kohnert, 2008;Hoff et al, 2008;Mariscal & Gallego, 2013;Roy & Chiat, 2004; prosodic structure (Chiat & Roy, 2007); phonotactic probability (McKean, Letts & Howard, 2013;Rispens, Baker & Duinmeijer, 2015); and wordlikeness (similarity of nonwords to actual words) (Frisch, Large & Pisoni, 2000). Thus, it is to be expected that the developmental trajectory of nonword repetition is influenced by a variety of factors (Chiat, 2006).…”
Section: Introductionmentioning
confidence: 99%